2012
DOI: 10.1371/journal.pone.0036200
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides Impair Insulin Gene Expression in Isolated Islets of Langerhans via Toll-Like Receptor-4 and NF-κB Signalling

Abstract: BackgroundType 2 diabetes is characterized by pancreatic β-cell dysfunction and is associated with low-grade inflammation. Recent observations suggest that the signalling cascade activated by lipopolysaccharides (LPS) binding to Toll-Like Receptor 4 (TLR4) exerts deleterious effects on pancreatic β-cell function; however, the molecular mechanisms of these effects are incompletely understood. In this study, we tested the hypothesis that LPS alters insulin gene expression via TLR4 and nuclear factor kappa-light-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
92
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 62 publications
6
92
1
7
Order By: Relevance
“…Furthermore, a recent study showed that treatment with LPS inhibits insulin gene expression in rat and human pancreatic beta-cells in a TLR4-dependent manner and via NF-κB signaling [45]. Importantly, the effects of LPS on the insulin gene in human islets were observed at concentrations similar to the circulating levels achieved during endotoxemia, suggesting that direct repression of the insulin gene might contribute to the metabolic disturbances associated with alterations of microbiota [45].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, a recent study showed that treatment with LPS inhibits insulin gene expression in rat and human pancreatic beta-cells in a TLR4-dependent manner and via NF-κB signaling [45]. Importantly, the effects of LPS on the insulin gene in human islets were observed at concentrations similar to the circulating levels achieved during endotoxemia, suggesting that direct repression of the insulin gene might contribute to the metabolic disturbances associated with alterations of microbiota [45].…”
Section: Discussionmentioning
confidence: 96%
“…The underlying mechanism of this inhibition requires further investigations, though it has already been described that HERV-W-Env exerts its pathogenic effects through an interaction with the TLR4 receptor (35,36). From a T1D perspective, this mechanism appears relevant, as TLR4 is expressed by β cells (42)(43)(44). Moreover, the inhibition of insulin secretion following TLR4 stimulation has already been observed in human, rat, and mouse pancreatic β cells by using lipopolysaccharide (LPS), the prototypical ligand of TLR4 (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…From a T1D perspective, this mechanism appears relevant, as TLR4 is expressed by β cells (42)(43)(44). Moreover, the inhibition of insulin secretion following TLR4 stimulation has already been observed in human, rat, and mouse pancreatic β cells by using lipopolysaccharide (LPS), the prototypical ligand of TLR4 (42,43). Inhibition appeared related to the repression of key transcription factors for β cell functions, PDX-1 and Maf-A, in a TLR4-dependent manner and via NF-κB signaling pathway (43).…”
Section: Discussionmentioning
confidence: 99%
“…FFAs can activate the TLR4 receptors of adipocytes and macrophages, and the inflammatory effect of FFAs is blocked in TLR4-deficient cells [25]. In addition, lipopolysaccharide (LPS) inhibits beta-cell gene expression in a TLR4-dependent manner and via NF-κB signaling in pancreatic islets [26]. Inhibition of TLR4 reduces hypothalamic inflammation, accompanied by a reduction in hypothalamic resistance to leptin and improved insulin signal transduction in the liver [27].…”
Section: Discussionmentioning
confidence: 99%